Isolation and preliminary screening of endophytic fungi from Ficus carica for biocontrol and phosphate solubilization - Mohd Rosli, Norsalsabila; Abu Hasan Ashari, Khairul Izzah; Ahmad Azmi, Nur Sabrina (Zibeline International Publishing, 2020)
Fungal endophytes are a special group of symbionts that invade the internal environment of the host organism without causing any pathogenic symptoms. They increase the vigor of the plant while protecting them from several biotic and abiotic stress conditions such as herbivory, disease, and drought. In this study, endophytic fungi were isolated from fig (Ficus carica), a beneficial plant belongs to the family of Moraceae. This study was conducted to determine the potential of fungal endophytes of F.carica as biocontrol agents against selected phytopathogens Ganoderma boninense, Magnaporthe oryzae, and Fusarium verticillioides. Besides, endophytic fungi isolates were also screened to assess their ability as a phosphate-solubilizing agent. Results obtained revealed that a total of 11 fungal endophytes was successfully isolated from leaf, root, and stem samples of F.carica. The cultural-morphological identifications were carried out on the unknown fungal isolates. For the antagonistic test, S2-1 and R3-4 show a promising potential against those phytopathogens with more than 20% Percentage Inhibition Radial Growth (PIRG). Endophyte S2-1 exhibits the competition mechanism, while R3-4 expresses the antibiosis mechanism in suppressing the mycelium growth of phytopathogens. As for phosphate solubilization, 8 of 10 isolates show positive results as phosphate solubilizer with the highest PSI value 3.02±0.05 (S2-4).